(untitled) (Materiali di Estetica. Terza serie, 2023)
The homily presented here is dated 15 May 2022, Fifth Sunday of Easter. The light, the colours conveyed in Father Angelo’s words are certainly highly poetic; but they have more than just an aesthetic value. They are imbued with a religious aura, in a deep, intimately experienced sense. The light of Christian love transfigures everything, reverberates in gestures in words, figures and atmospheres that are always touching. His text is designed as a commentary on liturgical texts: passages from the Psalms and excerpts from the “Acts of the Apostles”, St Paul’s “First Letter to the Corinthians”, and the Saint John’s “Gospel”.